Adaptive Cartesian Methods for Modeling Airborne Dispersion - Wissink, Andrew; Kosovic, Branko; Berger, Marsha; Chand, Kyle; Chow, Fotini K. (Advanced Computational Infrastructures for Parallel and Distributed Adaptive Applications, 2009)
This chapter contains sections titled: Introduction Finite Element Numerical Solution Infrastructures Parallel Implementation Future Work Acknowledgments References